The undiagnosed potential clinically significant incidental findings of neck CTA: A large retrospective single-center study. Issue 43 (23rd October 2020) - Chen, Guangliang; Xue, Yunjing; Wei, Jin; Duan, Qing
Abstract : Abstract: To assess the prevalence and missed reporting rate of potential clinically-significant incidental findings (IFs) in the neck CTA scans. All consecutive patients undergoing neck CTA imaging, from January 1, 2017 to December 31, 2018, were retrospectively evaluated by a radiologist for the presence of incidental findings in the upper chest, lower head and neck regions. These incidental findings were subsequently classified into 3 categories in terms of clinical significance: Type I, highly significant, Type II, moderately significant; and Type III, mildly or not significant. Type I and Type II IFs were determined as potential clinically significant ones and were retrospectively analyzed by another 2 radiologists in consensus. The undiagnosed findings were designated as those that were not reported by the initial radiologists. The differences in the rate of unreported potential clinically significant IFs were compared between the chest group and head or neck group. A total of 376 potential clinically significant IFs were detected in 1, 698 (91.19%) patients, of which 175 IFs were classified as highly significant findings (Type I), and 201 (53.46%) as moderately significant findings (Type II). The most common potential clinically significant findings included thyroid nodules (n = 88, 23.40%), pulmonary nodules (n = 56, 14.89%), sinus disease (n = 39, 10.37%), intracranial or cervical artery aneurysms (n = 30, 7.98%), enlarged lymph nodes (n = 24, 6.38%), and pulmonary embolism (n = 19, 5.05%). In addition, 184 (48.94%) of them were not mentioned in the initial report. The highest incidence of missed potential clinical findings were pulmonary embolism and pathologic fractures and erosions (100% for both). The unreported rate of the chest group was significantly higher than that of the head or neck one, regardless of Type I, Type II or all potential clinically significant IFs (χ 2 = 32.151, χ 2 = 31.211, χ 2 = 65.286, respectively; P < .001 for all). Important clinically significant incidental findings are commonly found in a proportion of patients undergoing neck CTA, in which nearly half of these patients have had potential clinically significant IFs not diagnosed in the initial report. Therefore, radiologists should beware of the importance of and the necessity to identify incidental findings in neck CTA scans.